In search for potential antidiabetic compounds from natural sources: docking, synthesis and biological screening of small molecules from Lycium spp. (Goji). Issue 1 (January 2020) - Yalamanchili, Chinni; Chittiboyina, Amar G.; Haider, Saqlain; Vasquez, Yelkaira; Khan, Shabana; do Carmo, Jussara M.; da Silva, Alexandre A.; Pinkerton, Mark; Hall, John E.; Walker, Larry A.; Khan, Ikhlas A.
Abstract: Current clinical antidiabetic drugs, like rosiglitazone 1, have been implicated in some serious side effects like edema, weight gain, and heart failure, making it necessary to find alternative agents. Partial agonists of peroxisome-proliferator activated receptor-gamma (PPARγ) were determined to possess improved insulin sensitivity without undeseirable side-effects when compared to full agonists of PPARγ, like rosiglitazone 1 . The traditional Chinese medicine (TCM) plants, Goji ( Lycium barbarum and Lycium chinense ) are widely used for treating symptoms related to various diseases including diabetes and hypertension. Twenty-seven reported compounds from Goji were docked into both partial- and full-agonist binding sites of PPARγ. Amongst the docked compounds, phenylethylamide-based phytochemicals (5 –9 ) (termed as tyramine-derivatives, TDs) were found to possess good docking scores and binding poses with favorable interactions. Synthesis of 24 TDs, including three naturally occuring amides (6, 8, 9 ) were synthesized and tested for PPARγ gene induction with cell-based assay. Three compounds showed similar or higher fold induction than the positive control, rosiglitazone. Among these three active TDs, trans-N -feruloyloctopamine (9) and tyramine derivatives-enriched extract (TEE ) (21%) of the root bark of L. chinense were further studied in vivo using db/db mice. However, both TEE as well as 9 did not show significant antidiabetic properties in db/db mice. In vivo results suggest that the proposed antidiabetic property of Lycium species may not be due to tyramine derivatives alone. Further studies of tyramine derivatives or enriched extract(s) for other bioactivities like hypocholesterolemic activities, and studies of novel isolated compounds from Goji will enable a more complete understanding of their bioactivities. Abstract : Natural product chemistry; Organic chemistry; Pharmaceutical chemistry; Diabetes mellitus; Wolfberry; Cercosporamide; Tyramines; Schrödinger; EchoMRI.